HGG-12. Rapid PTEFb-dependent transcriptional reorganization underpins the glioma adaptive response to radiotherapy. (3rd June 2022) - Walker, Faye; Sobral, Lays Martin; Danis, Etienne; Sanford, Bridget; Balakrishnan, Ilango; Wang, Dong; Pierce, Angela; Karam, Sana; Serkova, Natalie; Foreman, Nicholas; Venkataraman, Sujatha; Dowell, Robin; et al.
Abstract: BACKGROUND: Dynamic regulation of gene expression is fundamental for cellular adaptation to exogenous stressors. PTEFb-mediated promoter proximal pause-release of Pol II is a conserved regulatory mechanism for synchronous transcriptional induction best described in response to heat shock, but this pro-survival role has not been examined in the applied context of cancer therapy. DESIGN/METHOD: In order to examine the dynamics of chromatin reorganization following radiotherapy, we performed a combination of ChIP-, ATAC-, and RNA-seq in model systems of diffuse intrinsic pontine glioma (DIPG) and other pediatric high-grade gliomas (pHGG) following IR exposure. We interrogated IR-induced gene expression in the presence or absence of PTEFb blockade, including both mechanistic and functional consequences of concurrent inhibition or genetic depletion. We utilized culture models with live cell imaging to assess the therapeutic synergy of PTEFb inhibition with IR, as well as the therapeutic index of this intervention relative to normal controls. Finally, we employed orthotopic models of pHGG treated with conformal radiotherapy and CNS-penetrant PTEFb inhibitors in order to assess tolerability and anti-tumor effect in vivo. RESULTS: Rapid genome-wide redistribution of active chromatin features and PTEFb facilitates Pol II pause-release to drive nascent transcriptional induction within hours of exposure to therapeutic ionizing radiation. Concurrent inhibition of PTEFb imparts a transcription elongation defect, abrogating canonical adaptive programs such as DNA damage repair and cell cycle regulation. This combination demonstrates a potent, synergistic therapeutic potential agnostic of glioma subtype, leading to a marked induction of tumor cell apoptosis and prolongation of xenograft survival. CONCLUSION: These studies reveal a central role for PTEFb underpinning the early adaptive response to radiotherapy, opening new avenues for combinatorial treatment in these lethal malignancies.